The future of Nigerian university system (2024)
The Nigerian University System (NUS) currently comprises a total of 264 Universities, 53 of which are owned by the Federal Government, 62 owned by the various State Governments while the remaining 149 are Privately owned. The total student population is in the region of Two Million and Five Hundred Thousand. In this lecture, we have examined the issue of access, quality, funding and governance as they affect the NUS. Interrogating data published by the Joint Admissions and Matriculation Board (JAMB) over the period 2017 to 2023 we present quantitative, verifiable and objective assessment of addressing the question of equity in the adoption of Educationally-Less- Developed-States (ELDS) as a criterion for the selection of candidates for admission into undergraduate programmes in Nigerian Federal Universities. A trend analysis of contemporary events shows that the Nigerian University System will continue to grow, rather haphazardly and in an unplanned manner, in leaps and bounds especially in terms of student enrollment. Without a concomitant strengthening of leadership and governance, a substantial increase in funding for teaching and learning facilities, conduct of advanced research that is locally relevant and globally competitive (including but not limited to issues of food security, lagging economic development, climate change, reduction of carbon emission, natural resources degradation, insecurity), payment of decent wages to the knowledge workers amidst the continued exodus of the best and the brightest from the country, quality and relevance of the Universities in ensuring sustainable socio-economic development might suffer. A major feature of the Public Universities (Federal- and State-owned) which currently accounts for about 95% of the total student enrollment is incessant strikes by members of the various staff unions which has led to a cumulative loss of six years and three months in the last 32 years. Funding has been implicated as the root cause of these strikes. In order to be competitive there should be synergy between the Governments as university proprietors for a moratorium on these disruptive strikes. Conscious efforts should be made to internationalise in terms of student enrollment and the recruitment of academic staff. Some of the States on the current list of ELDS, in particular Kwara and Kogi, have posted excellent results and are now in the First Quartile justifying that they ought to be taken off the list. The same applies to Nasarawa which is in the Second Quartile. On the other hand, Lagos and the Federal Capital Territory are in the Fourth Quartile and if the ELDS is to be retained both should be included in the list. The National Council on Education should take a closer look at this recommendation with a view to implementing same. To the extent that the absence of a Governing Council hampers the proper functioning of a University and is an anathema to University Autonomy, it is our considered recommendation that the National Assembly should as a matter of urgent national importance amend the Universities (Miscellaneous Provisions) (Amendment) Act, 2003 in Section 2A as to provide that if the Council of a Federal University is dissolved, a new Council shall be constituted not later than three months.